Climate policies: A burden or a gain? - Thierry Bréchet; Henry Tulkens (Fondazione Eni Enrico Mattei (FEEM), 2013)
That climate policies are costly is evident and therefore often creates major fears. But the alternative (no action) also has a cost. Mitigation costs and damages incurred depend on what the climate policies are; moreover, they are substitutes. This brings climate policies naturally in the realm of benefit-cost analysis. In this paper we illustrate the direct cost components of various policies, and then confront them with the benefits generated, that is, the damage cost avoided. However, the sheer benefit-cost criterion is not a sufficient incentive to induce cooperation among countries, a necessary condition for an effective global climate policy. Thus, we also explore how to use this criterion in the context of international climate cooperation.
Keywords: Q54; H87; D61; D9; F42; Q2; 330; Climate Policy; Integrated Assessment; Cost-Benefit Analysis; Climate Cooperation